IMPROVING FORMULATION OF ARTHROBOTRYS DACTYLOIDES, A NEMATODE-TRAPPING-FUNGUS, IN KAOLIN-ALGINATE GRANULES - Sudirman1 . (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2009)
ABSTRACT This research aimed at evaluating performance of Arthrobotrys dactyloides in improved kaolin-alginate granular formulation. A. dactyloides was formulated in kaolin-alginate granules enriched with three types of organic matters (saw dust, rice hay, and corn cob), each with two concentrations (1% and 3% (w/v)). A formulation of granule without organic matter was also provided as a control. For each formulation, one half of granule was air-dried directly and the other half was given additional treatment, re-fermentation. The granules were used in experiments to observe performance of A. dactyloides in the formulations both in agar medium and in soil tests. All experiments were conducted with completely randomized design and data were analyzed with analysis of variance. Results showed that neither types nor concentrations of organic matters had any significant effect on the performance of A. dactyloides. Re-fermentation of granules, however, significantly improved weight of granules, number of propagules in granules, vigor of the fungus, growth of the fungus in soil, spore and ring production in soil. ABSTRAK Penelitian ini bertujuan untuk mengevaluasi performa Arthrobotrys dactyloides dalam formulasi butiran kaolin-alginat yang diperkaya. A. dactyloides diformulasikan dalam butiran kaolin-alginat yang diperkaya dengan tiga macam bahan organik (serbuk gergaji, jerami padi, dan tongkol jagung), masing-masing dengan dua konsentrasi (1% dan 3% (b/v)). Formulasi tanpa penambahan bahan organik disiapkan sebagai kontrol. Untuk tiap formulasi, setengah dari butiran langsung dikering-anginkan dan sisanya diberikan perlakuan tambahan, re-fermentasi. Butiran digunakan pada percobaan-percobaan untuk mengetahui performa A. dactyloides dalam formulasi, baik pada pengujian di media agar maupun di dalam tanah. Semua percobaan dilaksanakan dengan rancangan acak lengkap dan data dianalisa dengan analisis keragaman. Hasil penelitian menunjukkan bahwa tipe bahan organik atau konsentrasinya tidak berpengaruh nyata terhadap performa A. dactyloides. Sebaliknya, re-fermentasi butiran secara nyata meningkatkan berat butiran, jumlah propagul dalam butiran, vigor jamur, pertumbuhan jamur di dalam tanah, produksi spora dan cincin perangkap di dalam tanah.